The Assessment of Light Environment with the First Generation Leds - Olga E. Zheleznikova; Svetlana A. Mikaeva; Sergey N. Ageev; Ivan V. Blenstov; Olga S. Voynova (IAES Indonesian Section, 2018)
The article describes experimental studies on the effectiveness of lighting installations (LI) with light-emitting diodes (LEDs). It is established that LED-based lighting does not cause a negative impact on the organ of vision and the human body as a whole. The changes in the functional parameters of the organ of sight, which occur during the visual performance has the corresponding limits of physiological fluctuations and are reversible. The integral indicators of the efficiency of LED-based lighting were estimated. The practical significance of the results was shown.